Analysis of Factors Associated with the Use of Long Term Contraceptive Metode - Rahmatia, Sinta Dwi; Dinengsih, Sri; Lail, Nurul Husnul (Universitas Islam Lamongan, 2022)
The population problem faced by Indonesia is the high Population Growth Rate (LPP) and Total Fertility Rate (TFR). The use of MKJP is very appropriate to be applied to the condition of Indonesia which is experiencing population growth problems. The low use of MKJP in Indonesia is caused by many factors. In TPMB